Local Intraluminal Irrigation With Argatroban During Free Flap Repair in a Patient With Heparin-Induced Thrombocytopenia. (May 2017) - Macias, David; Kwon, Daniel I.; Walker, Paul C.; Peterson, Nathaniel R.
Objective: This study describes a case of a successful free flap repair using argatroban for local intraluminal irrigation as a substitute to heparin in a patient with heparin-induced thrombocytopenia. Methods: Case report and review of literature. Results: The patient had an uneventful postoperative course, and the free flap survived without complications. Conclusions: The use of argatroban during microvascular surgery is likely to be safe and simple and may be effective in preventing micro-thrombotic complications during microvascular surgery, and it should be considered as an alternative to heparinized saline for local intraluminal irrigation.